2018
DOI: 10.1039/c7ra13577g
|View full text |Cite
|
Sign up to set email alerts
|

Highly photoluminescent and stable silicon nanocrystals functionalized via microwave-assisted hydrosilylation

Abstract: Herein, we report a microwave-assisted hydrosilylation (MWH) reaction for the surface passivation of silicon nanocrystals (Si-NCs) with linear alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…A lifetime of ∼125 µs at ∼825 nm was reported for alkylterminated SiNCs with AQY of ∼65% [19]. A lifetime of ∼155 µs at ∼860 nm was reported also for alkyl-terminated SiNCs with maximum AQY of ∼39% [48]. Furthermore, τ ∼65 µs at 800 nm, for PSi having an AQY of 32% (peak wavelength 685 nm) [14].…”
Section: Resultsmentioning
confidence: 82%
“…A lifetime of ∼125 µs at ∼825 nm was reported for alkylterminated SiNCs with AQY of ∼65% [19]. A lifetime of ∼155 µs at ∼860 nm was reported also for alkyl-terminated SiNCs with maximum AQY of ∼39% [48]. Furthermore, τ ∼65 µs at 800 nm, for PSi having an AQY of 32% (peak wavelength 685 nm) [14].…”
Section: Resultsmentioning
confidence: 82%
“…where N em and N abs is number of emitted and absorbed photons respectively, was measured using method described by de Mello et al 35,50,51 In detail, the LED beam was focused by a lens and directed into an integrating sphere (Labsphere) with a diameter of 15 cm. An optical fiber with a diameter of 1 mm (FP1000URT, Thorlabs) was used to collect the emission from integrating sphere and transfer it to the spectrometer (AvaSpec-ULS2048x64TEC, Avantes).…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…34 In our previous work, we have demonstrated that microwave-assisted hydrosilylation (MAH) method can produce SiNc exhibiting a PLQY of up to 40% and excellent long-term stability (6 months without decrease of PLQY). 35 In this article, we describe an approach to attach functional dyes to the core of SiNc via hydrosilylation reaction using a microwave (MW) reactor. As a result, we observed significant enhancement of SiNc NIR PL upon excitation with blue and green light.…”
Section: Introductionmentioning
confidence: 99%
“…During this annealing process, the nucleation of SiNCs seeds inside a silicon dioxide matrix occurs (Hessel et al, 2012 ). Details regarding the annealing procedure can be found in the literature (Beri et al, 2018 ). After annealing, the sample was transferred to an agate mortar and ground.…”
Section: Methodsmentioning
confidence: 99%